Effect of Low Price on Respondents While Purchasing FMCG Products: An Empirical Study - Singh, Amrinder; Jewandah, Simran; Singh, Amandeep (International Journal of Psychosocial Rehabilitation, 2020)
A large portion of the organizations falls into the value trap as they feel it is the most effortless technique for the division. It is difficult to get this right. Numerous effective organizations contend on cost since that is the simplest alternative or, if nothing else, the one that takes the least reasoning. There is an expanding pattern for organizations to build up the enormous box experience that is modest in value, low on administration, and low on separation. Be that as it may, what number of items can be named where the least expensive model is the market leader? As opposed to going down that way, the organizations have recognized that contending on cost alone is not, at this point, feasible. This exploration paper attempts to feature the impact of low cost on the respondents, regardless of whether the item is being bought as a result of low cost or not.